2010
DOI: 10.1007/s10846-010-9492-x
|View full text |Cite
|
Sign up to set email alerts
|

Towards Autonomous Micro UAV Swarms

Abstract: Micro Unmanned Aerial Vehicles (UAVs) such as quadrocopters have gained great popularity over the last years, both as a research platform and in various application fields.However, some complex application scenarios call for the formation of swarms consisting of multiple drones. In this paper a platform for the creation of such swarms is presented. It is based on commercially available quadrocopters enhanced with on-board processing and communication units enabling full autonomy of individual drones. Furthermo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
65
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(65 citation statements)
references
References 8 publications
0
65
0
Order By: Relevance
“…Aside from the Technical University of Braunschweig, Germany, the Fraunhofer Institute, Karlsruhe, Germany, the ETH Zurich, Switzerland, as well the University of Pennsylvania, Philadelphia, PA, USA, and the Center for Collaborative Control of Unmanned Vehicles at the University of California, Berkeley, CA, USA are all working in the field of UAS swarm intelligence (Bürkle et al, 2011;Schattenberg et al, 2011;Schoellig et al, 2012;Kushleyev et al, 2012). In the future, multiple vehicle units will also be capable of path planning and interacting within a whole fleet (Barrientos et al, 2011;Cartade et al, 2012).…”
Section: Autonomous Platforms and Swarm Technologymentioning
confidence: 99%
“…Aside from the Technical University of Braunschweig, Germany, the Fraunhofer Institute, Karlsruhe, Germany, the ETH Zurich, Switzerland, as well the University of Pennsylvania, Philadelphia, PA, USA, and the Center for Collaborative Control of Unmanned Vehicles at the University of California, Berkeley, CA, USA are all working in the field of UAS swarm intelligence (Bürkle et al, 2011;Schattenberg et al, 2011;Schoellig et al, 2012;Kushleyev et al, 2012). In the future, multiple vehicle units will also be capable of path planning and interacting within a whole fleet (Barrientos et al, 2011;Cartade et al, 2012).…”
Section: Autonomous Platforms and Swarm Technologymentioning
confidence: 99%
“…Bürkle et al (2011) tested a two operator console that allowed operator customization to fit several types of possible missions or UAV swarms. By sharing responsibilities between two individuals, the researchers found that operators had a lower cognitive workload and felt more effective at controlling the swarm.…”
Section: Results For Rq3mentioning
confidence: 99%
“…Several papers examined the possibility of spreading the work among multiple operators. For Bürkle et al (2011), giving two individuals joint responsibility for a swarm was effective at reducing cognitive tunneling and the loss of SA that comes with it. Their small study divided responsibilities between a pilot, who controlled the UAV swarm's flight and sensor focus, and an analyst, who "obtain[ed] and ke[pt] an overview of the situation and inform [ed] the higher authorities about important discoveries" (Bürkle et al, 2011, p. 346).…”
Section: Reducing Cognitive Workloadmentioning
confidence: 99%
See 1 more Smart Citation
“…Some technological improvements are still required to this end: charging base stations at the end of each pipe leg, autonomous decision capacity for recharge or return to base in case of too bad weather conditions. Work on that direction has already been done (Bürkle et al 2011), and the feasibility of the small UAV swarm technology has been tested, demonstrating capacity of individual vehicles to collect and use data whilst communicating with each other to support a unified mission. Once the technology matures, swarms of small UAVs are expected to be particularly useful in rescue operations (Qi et al 2015).…”
Section: Platformmentioning
confidence: 99%